The Impact of Educational Technology on Behavioural Engagement in English Learning: A Systematic Literature Review - Damayanti, Komang Devi; Adnyayanti, Ni Luh Putu Era; Mahayanti, Ni Wayan Surya (Lembaga Pengembangan Kinerja Dosen, 2026)
This systematic literature review analyzes previous studies on impact of educational technology on students’ behavioural engagement in English language learning. The integration of educational technology in English classroom has increased significantly in order to address students’ low participation, limited attention, and passive learning behaviour. Various digital tools such as digital storybooks, digital storytelling, multimedia learning platforms, and interactive online applications have been implemented to promote students’ active participation. This review followed the prefered Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to ensure a systematic and transparent review process. Relevant journal articles published between 2020 until 2025 were identified through Google Scholar, ResearchGate, and Publish or Perish. A total of 15 articles met the conclusion criteria and were analysed in this study. The findings indicate that educational technology positively influences students’ behavioural engagement, which is reflected in increased participation, attention, interaction, and task completion in English leraning contexts.The review higlights that the appropriate intergration of educational technology can support more interactive and learner-centred English language learning environments.